The role of osteoprotegerin in arthritis - Schett, Georg (BioMed Central, 2003)
Bone erosion is a hallmark of rheumatoid arthritis. Recent evidence from experimental arthritis suggests that osteoclasts are essential for the formation of local bone erosions. Two essential regulators of osteoclastogenesis have recently been described: the receptor-activator of nuclear factor kappa B ligand, which promotes osteoclast maturation, and osteoprotegerin (OPG), which blocks osteoclastogenesis. The present review summarizes the current knowledge on the role of osteoclasts in local bone erosion. In addition, the role of OPG as a therapeutic tool to inhibit local bone erosion is addressed. Finally, evidence for OPG as an inhibitor of systemic inflammatory bone loss is discussed.